On the compactness via primal topological spaces - Ohud Alghamdi (AIMS Mathematics)
In this paper, we introduce new concepts, including $ \mathfrak{P} $-compactness, strongly $ \mathfrak{P} $-compactness, and super $ \mathfrak{P} $-compactness, in view of a primal topological space structure. We provide some results regarding to these concepts. Additionally, some examples are presented to illustrate the relations between these concepts.